Pendidikan Kader Penggerak Nahdlatul Ulama as a Contemporary Nationalism Movement for Nu's Young Generation - Chadziq, Achmad Lubabul; Munir, Misbahul (IKIP PGRI Bojonegoro, 2022)
Abstract: This study explains the form of the spirit of nationalism of the millennial generation which is based on the training activities of NU driving cadres. The basis of this activity is a response to the form of radicalization and also the issue of the existence of an organizational community that wants to replace Indonesia as a caliphate state. This study uses a mixed method which focuses on data collection and analysis and combines quantitative data and qualitative data. The result of this study is that the attitude of the NU Mobilizing Cadre Nationalism in Gresik Regency is very good and this attitude is dominated by the type of Religious Nationalism where nationalism that obtains political legitimacy from religious equality with the existence of a motto (hub al wathon min al iman). Second, the spirit of nationalism of NU Gresik cadres is carried out with various agendas, both formal and non-formal, by carrying out socio-religious activities with the aim of maintaining religion and the integrity of the state, Pancacila, Undang-Undang 1945 and Bhineka Tunggal Ika.Keywords: Education, Nationalism, ReligionAbstrak: Kajian ini menjelaskan tentang bentuk semangat nasionalisme genereasi millennial yang didasarkan pada kegiatan pelatihan kader penggerak NU. Dasar kegiatan ini merupakan respon dari adanya bentuk radikalisasi dan juga isu tentang adanya komunitas faham organisasi yang ingin menggantikan Indonesia sebagai negara khilafah. Kajian ini menggunakaan metode campuran dimana berfokus pada pengumpulan dan analisis data serta memadukan antara data kuantitatif dan data kualitatif. Hasil Kajian ini adalah sikap Nasionalisme Kader Penggerak NU di Kabupatan Gresik sangatlah baik dan sikap tersebut didominasi dengan tipe Nasionaliosme Agama dimana nasionalisme yang memperoleh legitimasi politik dari persamaan agama dengan adanya semboyan (hub al wathon min al iman). Kedua, semangat nasionaslisme kader NU Gresik diwujdukan dengan berbagai agenda baik secara formal ataupun non-formal dengan melakukan kegiatan sosial keagamaan dengan tujuan menjaga agama dan keutuhan negara, Pancacila, Undang-Undang Dasar 1945 dan Bhineka Tunggal Ika.Kata Kunci: